2003
DOI: 10.1210/jc.2002-020511
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenase Activity in Hypothalamic Obesity

Abstract: After extensive suprasellar operations for hypothalamic tumor removal, some patients develop Cushing-like morbid obesity while they receive replacement doses of glucocorticoids. In this study, we examined the hypothesis that target tissue conversion of inactive 11-ketosteroids to active 11 beta-OH glucocorticoids might explain the obesity of some patients with hypothalamic lesions. Toward this aim, we studied 10 patients with hypothalamic obesity and secondary adrenal insufficiency and 6 control Addisonian pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 23 publications
1
48
0
5
Order By: Relevance
“…11b-HSD activity in vivo is often assessed by the urinary (THFC5a-THF)/ THE ratio. However, several studies suggested that this ratio is an inadequate indicator of 11b-HSD1 activity (32,33), because it is determined also by 11b-HSD2 and A-ring reductases, and should therefore be interpreted as the balance between 11b-HSD activities in all tissues. In adult obesity, several studies have been performed regarding 11b-HSD activity (33,34), but studies in obese children are still missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11b-HSD activity in vivo is often assessed by the urinary (THFC5a-THF)/ THE ratio. However, several studies suggested that this ratio is an inadequate indicator of 11b-HSD1 activity (32,33), because it is determined also by 11b-HSD2 and A-ring reductases, and should therefore be interpreted as the balance between 11b-HSD activities in all tissues. In adult obesity, several studies have been performed regarding 11b-HSD activity (33,34), but studies in obese children are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described decreased urinary THFC5a-THF/THE ratios with increasing BMI in simple obesity in adults, and this was interpreted as a decreased 11b-HSD1 reductase activity (37,38). However, other studies have failed to show this relationship (40)(41)(42)(43) and, indeed, positive correlations between urinary ratio and BMI have also been described (19,32,39). The explanation for this discrepancy is not clear yet, but it is possible that this is due to variations in A-ring reductase activities or by tissue-specific alterations of 11b-HSD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urinary metabolite ratios as used in some studies should be taken with caution as an indicator for 11β-HSD activity and do not correlate with BMI but only with the ratio of visceral to subcutaneous fat, e.g. as measured by computerised tomography [56]. Genetic analyses of microsatellite markers within the 11β-HSD1 gene showed associations with cortisol metabolite ratios and WHR indicating a possible contribution of 11β-HSD1 to the development particularly of visceral obesity.…”
Section: Dysregulation Of 11β-hsd1 In Human Obesitymentioning
confidence: 99%
“…7 Mice overexpressing 11bHSD-1 in adipocytes demonstrate increased adipose tissue corticosterone (the active metabolite in mice), hyperphagia, greater weight gain (particularly when given a high fat diet), increased accumulation of visceral adipose tissue, insulin resistance, and increased expression of lipoprotein lipase in omental fat. 7 We have recently observed an abnormally high ratio of urinary cortisol/cortisone metabolites in patients with hypothalamic obesity, 8 suggesting an enhanced activity of 11bHSD-1. Other studies show that a higher BMI is associated with increased inactivation of cortisol in the liver of obese men and women, 9,10 as demonstrated by higher excretion of cortisol metabolites, accompanied by decreased activity of 11bHSD-1 in liver, but a marked enhancement of 11bHSD-1 activity in subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%